Social Media Usage On MSMEs' Performance: The Moderating Role Of Innovation Capability - Yordan Hermawan Apidana; Dian Rusvinasari (Jurnal Manajemen, 2024)
This study aims to determine whether using social media such as TikTok, Instagram, and Facebook can improve the performance of MSMEs if innovation capability is used effectively. The research employs a quantitative approach, involving 300 respondents who are MSME owners or managers in Kebumen Regency. The analysis utilizes the Partial Least Square (SmartPLS) method to assess the seven hypotheses proposed in this study. The results indicate that social media platforms like TikTok, Instagram, and Facebook positively influence MSMEs' performance. Additionally, innovation capability exhibits a positive impact on MSMEs' performance. Furthermore, innovation capability moderates the connection between Instagram usage and MSMEs' performance. However, it does not exert a similar moderating effect on the relationship between TikTok and Facebook usage and MSMEs' performance. These findings offer valuable insights for MSME owners and managers, enabling them to navigate and leverage the evolving landscape of social media marketing to maintain their competitiveness and performance.